2015
DOI: 10.1111/apha.12491
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electrical vs. chemical deep brain stimulation at midbrain sites on micturition in anaesthetized rats

Abstract: Electrical deep brain stimulation within the midbrain can inhibit reflex micturition. We suggest that the applied stimulus entrained activity in the neural circuitry locally, thereby imposing an unphysiological pattern of activity. In a way similar to the use of electrical signals to 'jam' radio transmission, this may prevent a synchronized pattern of efferent activity being transmitted to the spinal outflows to orchestrate a coordinated voiding response. Further experiments to record neuronal firing in the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 37 publications
4
20
0
Order By: Relevance
“…The present study was designed to compare the effectiveness of high‐frequency stimulation of the S1 root and the pelvic nerve to inhibit voiding. As reported previously by us and by others, continuous infusion of saline into the bladder evoked repeated voiding . In addition, we observed contraction of the external oblique musculature of the abdominal wall during voiding.…”
Section: Discussionsupporting
confidence: 89%
“…The present study was designed to compare the effectiveness of high‐frequency stimulation of the S1 root and the pelvic nerve to inhibit voiding. As reported previously by us and by others, continuous infusion of saline into the bladder evoked repeated voiding . In addition, we observed contraction of the external oblique musculature of the abdominal wall during voiding.…”
Section: Discussionsupporting
confidence: 89%
“…A number of previous studies have shown the vlPAG as the column responsible for sensorimotor communication with the bladder. [8][9][10][11][12][13] We could reproduce these findings in our experimental setting, as our data showed a significant increase in c-Fos-positive cells in this subregion after bladder stimulation. Furthermore, our results highlighted the role of glutamatergic cells in relation to bladder-PAG circuitry.…”
Section: Discussionsupporting
confidence: 72%
“…10 Chemical stimulation of the vlPAG by D,L-homocysteic acid in rats increased the frequency of micturition. 11 Stereotaxic injections of the inhibitory mediator, cobalt chloride, into the caudal vlPAG reversibly attenuated bladder contractions and external urethral sphincter electromyographic activity in rats. 12 Injection of other inhibitory or stimulatory agents, CoCl2 and L-glutamate, into the vlPAG of rats resulted in the suppression or stimulation of micturition, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The latency of PAG activation after PNL stimulation in the current study ( Figure 4A) is consistent with that (33-47 ms) reported in previous studies by Noto et al 24,25 . Thus, in contrast to the inhibitory function of the ACC, PAG is likely to have a facilitatory effect on the micturition reflex, as suggested by human brain imaging and animal studies 26,27 .…”
Section: Discussionmentioning
confidence: 99%